In situ formed microparticles of PLGA from O/W emulsions stabilized with PVA: Encapsulation and controlled release of progesterone - Turino, Ludmila Noelia (2014)
In situ-formed microspheres are an alternative to expensive and complex manufactured preformed systems for the controlled release of drugs. The aim of this study was to evaluate the potential of stable O/W emulsions to entrap progesterone after in vitro precipitation of poly(d,l-lactide-co-glycolide) (PLGA) microparticles. This was achieved by a solvent selection based on their miscibility and capability to solubilize the drug and PLGA. Stability assays, size distribution studies, and progesterone encapsulation efficiency evaluation were carried out for the candidate formulations. After selection of the most suitable formulations, in vitro-controlled release test of progesterone were done. Results demonstrate that emulsions based on triacetin and polyvinyl alcohol (PVA) aqueous solutions were useful solvent systems to obtain microspheres capable to deliver the hormone in a controlled release manner. In addition, for the first time, for these authors, PVA was successfully implemented into a continuous phase to increase the stability of in situ-formed O/W formulations.